MULTI-LEVEL MODELS OF QUALITY MANAGEMENT IN HIGHER VOCATIONAL EDUCATION INSTITUTIONS - Murodov Nodirbek Oybek o‘g‘li (Journals Park Publishing, 2023)
To control and manage the quality of the educational institution, to meet the standard requirements, quality management systems are formed in higher vocational education institutions, and the evaluation and management mechanism was established. This article covers this process in detail.
Keywords: Higher education, mission, quality management, forecasting, expertise, modeling, standards, methodology, corporate system.